2022
DOI: 10.4103/jfmpc.jfmpc_2333_21
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive structured training on occupational health hazards and vaccination

Abstract: Introduction: Healthcare providers are vulnerable to occupational health hazards. However, they do not appropriately apprehend the serious health consequences of occupational exposures. This study was conducted to assess the effectiveness of “Occupational health hazards and vaccination” workshop organized periodically in institute. Material and Methods: We validated the questionnaire prior to assess the effectiveness of workshop. Expert performed “key check” of question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the present study, we included the most important constructs of the PMT for preparing and delivering the education content to emergency ward nurses. Another study in India also revealed that educational workshops improved HCWs’ knowledge about occupational hazards [ 26 ]. A literature review study also highlighted the positive impacts of e-training programs on employees’ knowledge and behavior regarding occupational health and safety and reducing workplace injuries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we included the most important constructs of the PMT for preparing and delivering the education content to emergency ward nurses. Another study in India also revealed that educational workshops improved HCWs’ knowledge about occupational hazards [ 26 ]. A literature review study also highlighted the positive impacts of e-training programs on employees’ knowledge and behavior regarding occupational health and safety and reducing workplace injuries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%